The use of technology in learning to increase interest in learning social sciences - Prasetya, Robby (Maliki Interdisciplinary Journal, 2024)
In the current era of technological development, there are many activities that can be carried out in more effective ways, one of which is learning. However, sometimes the easy access to technology is not used wisely. Apart from that, the phenomenon of dissolving attitudes of nationalism and patriotism also contributes to concern. Based on this background, this study aims to identify the status quo of technology use and attitudes of nationalism and patriotism in the younger generation, and also to find out how to learn Social Sciences through the use of technology. This study uses a conceptual approach using several sources of literature related to the issues discussed. This research concludes that the values of nationalism and patriotism by the younger generation have faded and the use of technology has not been utilized optimally. In addition, the way to increase interest in learning Social Education Sciences can be through social media with a more practical and interesting presentation pattern.